Effect of herbicides based on glyphosate on the photosynthesis of green macroalgae in tropical lotic environments - Oliveira, Régis de Campos [UNESP]; Boas, Lucas Kortz Vilas [UNESP]; Branco, Ciro Cesar Zanini [UNESP] (Schweizerbart, 2021)
The susceptibility of aquatic environments to contamination by glyphosate has been of worldwide con-cern, mainly since this herbicide affects important physiological processes such as photosynthesis. Considering this, we evaluated the effects of two forms of glyphosate (technical grade and Roundup®) on the photosynthesis of four lotic green macroalgae (Nitela subglomerata, Oedogonium sp., Spirogyra sp., and Desmidium grevillei) after seven days of exposure. The photosynthetic ability of these macroalgae was analyzed by photochemical performance using the chlorophyll-a fluorescence and chlorophyll-a content techniques. The results showed that Roundup® reduced the chlorophyll-a content of macroalgae and affected more specimens when compared to tech-nical-grade glyphosate. According to these results, we suggest that the presence of glyphosate-based herbicides in tropical streams might affect the photosynthesis of stream macroalgal communities, even in concentrations allowed by Brazilian law, which represent a great risk for the structural and functional dynamics of these ecosystems as a whole.
Keywords: Chlorophyll fluorescence; Chlorophyll-a content; Glyphosate; Maximal permissible concentration; Roundup®